2014
DOI: 10.1016/j.dld.2013.08.128
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors and subsequent risk of celiac disease

Abstract: Background The prevalence of celiac disease and the use of medications that inhibit acid secretion have both increased in recent decades. Aims To explore the association between antisecretory medication exposure and subsequent development of celiac disease. Methods In this population-based case control study, we identified patients with celiac disease diagnosed at all pathology departments in Sweden from July 2005 through February 2008. Patients were matched by age and gender with up to 5 controls. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 46 publications
2
37
0
3
Order By: Relevance
“…Given the possibility that PPIs may have been prescribed in response to symptoms of undiagnosed celiac disease, a sensitivity analysis excluding all PPI prescriptions in the one year immediately preceding this diagnosis found that the effect, though diminished, remained significant (OR 2.28; 95% CI 1.67–3.10). 75 While these results do not prove causality, the potentially mediating effect of the microbiome on the PPI-celiac disease relationship warrants further investigation.…”
Section: Effects Of Proton Pump Inhibitors On the Microbiomementioning
confidence: 84%
“…Given the possibility that PPIs may have been prescribed in response to symptoms of undiagnosed celiac disease, a sensitivity analysis excluding all PPI prescriptions in the one year immediately preceding this diagnosis found that the effect, though diminished, remained significant (OR 2.28; 95% CI 1.67–3.10). 75 While these results do not prove causality, the potentially mediating effect of the microbiome on the PPI-celiac disease relationship warrants further investigation.…”
Section: Effects Of Proton Pump Inhibitors On the Microbiomementioning
confidence: 84%
“…L'ipotesi è che, sia l'aumento del pH gastrico che l'aumento di permeabilità sulla mucosa dato da queste molecole, possano compromettere la digestione peptica e l'assorbimento di antigeni alimentari, con possibile ruolo nell'attivazione autoimmune della malattia nei soggetti predisposti. 168 In un altro ampio studio caso controllo svedese si è evidenziata una correlazione positiva (OR 1,30 IC 95%) tra esposizione ad antibiotici e MC che troverebbe una spiegazione nella disbiosi iatrogena in grado di alterare il microbiota intestinale e i suoi riconosciuti effetti immunologici. 153 Però, gli autori non traggono conclusioni definitive sul ruolo dei fattori iatrogeni nella MC in quanto la patologia riconosce una multifattorialità causale, con processi ancora in parte sconosciuti; inoltre l'analisi causa-effetto è confondente in quanto questi farmaci di per sé stessi sono utilizzati spesso in conseguenza alla malattia stessa.…”
Section: Eziopatogenesiunclassified
“…95, 96 The human diet contains numerous proteins with the potential to evoke immunological responses. Digestion of these potential food allergens normally begins in the stomach through the action of pepsin proteinases in acidic gastric juice.…”
Section: Ppi Use Might Predispose To the Development Of Eoementioning
confidence: 99%